PENGARUH RANTAI PENAWARAN TERHADAP KEPUASAN KONSUMEN PADA CV MULTI MANDIRI ANUGERAH PRATAMA MEDAN - KUANDI; NICHOLAS . (LP2MTBM MAKARIOZ, 2019)
CV Multi Mandiri Award Pretama Medan is a company that moves in the field of aluminum processing has an unfavourable supply chain system and always obtains raw materials that do not match the needs of its products, so that the company's ability to emnerap the flexibility of demand has not been applied well, besides, the relationship customer process has not been carried out well, so the products produced are still not in line with the consumer's expectations. As a result consumers feel dissatisfied when using the products of the CV Multi Mandiri Pretama and switching to using products from rival companies. This study aimed to find out whether improving the quality of the supply chain through the flexibility of demand, placement and customer relationships processes has a positive and significant impact on consumer satisfaction using by product at the CV Multi Mandiri Pretama Medan. The analysis of the data on this study used validity and reliability tests, double linear regression analysis and hypothetical tests, where the population in this study was a consumer CV Multi Mandiri Pratama of 750 people, whereas the method of withdrawal of the sample on this study used simple random sampling calculated using the slovin formula which in the end the number of successful samples was drawn by 40 consumers. The results of this study state that in a sense of demand flexibility and customer relationships processes have a positive and significant influence on consumer satisfaction using by product at CV Multi Mandiri Award Pretama Medan, whereas partially only variable roses customer relationships have a positive and significant influence on consumer satisfaction using by product at CV Multi Mandiri Award Pretama Medan